2006
DOI: 10.1158/1535-7163.mct-06-0113
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxyestradiol suppresses microtubule dynamics and arrests mitosis without depolymerizing microtubules

Abstract: 2-Methoxyestradiol (2ME2), a metabolite of estradiol-17B, is a novel antimitotic and antiangiogenic drug candidate in phase I and II clinical trials for the treatment of a broad range of tumor types. 2ME2 binds to tubulin at or near the colchicine site and inhibits the polymerization of tubulin in vitro, suggesting that it may work by interfering with normal microtubule function. However, the role of microtubule depolymerization in its antitumor mechanism of action has been controversial. To determine the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 25 publications
2
89
2
Order By: Relevance
“…At low therapeutic concentrations, 2ME2 inhibits microtubule dynamics, which leads to inhibition of the formation of the mitotic spindle apparatus, and consequently, to the arrest of cells in metaphase and induction of apoptosis (4,5,7). Therefore, the accumulation of cells in metaphase was measured by determining the mitotic index, measured as the percentage of cells with chromatin condensation.…”
Section: Effects Of 2me2 Analogues On Chromatin Condensationmentioning
confidence: 99%
See 1 more Smart Citation
“…At low therapeutic concentrations, 2ME2 inhibits microtubule dynamics, which leads to inhibition of the formation of the mitotic spindle apparatus, and consequently, to the arrest of cells in metaphase and induction of apoptosis (4,5,7). Therefore, the accumulation of cells in metaphase was measured by determining the mitotic index, measured as the percentage of cells with chromatin condensation.…”
Section: Effects Of 2me2 Analogues On Chromatin Condensationmentioning
confidence: 99%
“…2ME2 has been shown to inhibit the polymerization of tubulin in vitro, thus disrupting normal microtubule function (3). However, at therapeutic doses in vivo, the drug is likely to act by impairing microtubule dynamics (4,5). Given that rapid microtubule dynamics are essential for the correct assembly and function of the mitotic spindle, 2ME2 activates the spindle assembly checkpoint and causes metaphase arrest, and as a consequence, inhibition of cell proliferation and induction of cellular apoptosis (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, at low concentrations, 2ME2-induced mitotic block involved kinetic stabilization of microtubule dynamics rather than alteration of microtubule polymerization (10,11). Recently, Kamath et al (12) showed that, at low concentrations of 2ME2, mitotic cell arrest was due to suppression of microtubule dynamics and not depolymerization of microtubules. However, the binding site of 2ME2 on h-tubulin is far from clear.…”
Section: Introductionmentioning
confidence: 98%
“…It has undergone phase I and phase II clinical trials as an anti-mitotic and anti-angiogenic agent in various cancer types [3]. Kamath et al [4] demonstrated that 2ME suppressed microtubule dynamics at low concentrations, while higher doses resulted in microtubule Abstract Purpose 2-Methoxyestradiol (2ME) is a promising anticancer agent that disrupts the integrity and dynamics of the spindle network. In order to overcome the pharmacokinetic constraints of this compound, a panel of sulphamoylated estradiol analogues were in silico-designed by our laboratory.…”
Section: Introductionmentioning
confidence: 99%